Strategy For Intensifying Cash Waqf In Islamic Banking To Support Green Finance Programs In Indonesia - Aris Fauzin; Riadus Sholihin; Ade Ruslan Hidayat; , Khilda Lathifatul Hidayah (SEAN Institute, 2022)
Cash waqf has enormous potential in Indonesia. This can be seen from the data on the collection of cash waqf during the 2011-2018 period which reached Rp. 255 billion. In the last three years, namely 2018-2021, the figure rose to Rp. 855 billion, or an increase of 236 percent. This study intends to seek alternatives and innovations in finance, particularly Islamic finance to support the development of green finance in Indonesia. This paper will focus on the strategy of intensifying cash waqf in Islamic banking to support green finance programs in Indonesia. The research method used in this research is descriptive analysis method. The types of data used are library data and field data. The data sources are primary data and secondary data. Data collection techniques were carried out through interviews, literature studies, and documentation. Data analysis techniques used are editing, presentation, and interpretation of data. In this study, three options are offered that the government can do through cash waqf instruments in Islamic Banking to encourage green finance programs. First, making Islamic banks as nadzir waqf, not just as distribution partners. Second, encouraging Islamic banks to collaborate with nadzir waqf institutions to create waqf-based product development innovations. Third, make regulations regarding waqf obligations in Islamic banks